Short Communication: The bioinformatics perspective of Foeniculum vulgare fruit's bioactive compounds as natural anti-hyperglycemic against alpha-glucosidase - Fatchur Rohman (MBI & UNS Solo, 2020)
Abstract. Rohman F, Putra WE. 2021. Short Communication: The bioinformatics perspective of Foeniculum vulgare fruit's bioactive compounds as natural anti-hyperglycemic against alpha-glucosidase. Biodiversitas 22: 79-84. The management in controlling the blood glucose level is crucially necessary to be promoted. Many reports showed the harmful effect of glucose toxicity, most of them are the cluster of metabolic disorder. Nowadays, natural products are getting much attention on health issues. The uses of medicinal plants for drug materials are dramatically increasing. In our previous study about local medicinal plants identification, we found that Tengger Tribe in Indonesia uses numerous type of species, including Foeniculum vulgare which was widely found and occupied as traditional medicine by Tengger Tribe in the area of Taman Nasional Bromo Tengger Semeru, East Java, Indonesia. According to their local belief, F. vulgare has been used to ameliorate several types of diseases. Thus, in this present study, we aimed to virtually evaluate the bioactive compounds of F. vulgare for anti-hyperglycemic against the alpha-glucosidase. We performed computational prediction of ligands-protein interaction by molecular docking approaches. The 2D structure of ligands and 3D structure of target protein were retrieved via the database. The natural compound's structure was then evaluated by the Lipinski rule of five to indicate whether it can be categorized as drug-like or not. Moreover, according to our simulation, F. vulgare fruit's bioactive compounds including sterol, anethole, and fenchone might have therapeutic effect to reduce the hyperglycemia incidence by inhibiting the alpha-glucosidase activity. Compared to miglitol, an alpha-glucosidase inhibitor, Sterol have the most significant binding affinity against the alpha-glucosidase. Therefore, these findings suggest that sterol, anethole, and fenchone might be potential new candidates for alpha-glucosidase inhibitors.